Sosialisasi Game Edukatif Pasca Bencana Kebakaran sebagai Upaya Pemulihan Psikologis dan Semangat Belajar Siswa SDN 30 V Koto Kampung Dalam, Kabupaten Padang Pariaman - Umayrha Putri Madila; Thaira Khairani; Dhini Melviansyah; Rigo Winandri; Novita Efendi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This community service activity was carried out through the Kuliah Kerja Nyata (KKN) program at SDN 30 V Koto Kampung Dalam, Padang Pariaman Regency, West Sumatra. The activity aimed to restore the psychological condition and learning spirit of students who experienced trauma following a fire disaster. Five educational games were implemented, namely sendok tepung (spoon and flour), pipet aqua (straw transfer), naga balon (balloon dragon), biskuit Roma (biscuit game), and joget balon (balloon dance). These games were selected to stimulate physical, social, emotional, and mental aspects of students. The instruction was delivered directly using a microphone and speaker system, with a storytelling approach that sparked imagination rather than evoking pity. The impact was measured through behavioral observation, with positive indicators including students transitioning from drooping posture to upright, laughter replacing silence, and passive children beginning to vocalize and cheer. Results indicated that educational game-based socialization is effective as a non-therapeutic initial psychosocial recovery strategy for disaster-affected children. This activity demonstrates that simple and participatory methods can significantly contribute to restoring children's learning motivation and psychological resilience post-disaster.